Actinic cheilitis: Clinical and histological features - Cavalcante, Ana Sueli Rodrigues [UNESP]; Anbinder, Ana Lia; Carvalbo, Yasmin Rodarte [UNESP] (W B Saunders Co-elsevier Inc, 2008)
Purpose: The purpose of this study was to analyze the clinical and histological features of actinic cheilitis (AC).Patients and Methods: A total of 29 patients with AC were clinically evaluated, and incisional biopsies were performed to confirm the clinical diagnosis. Histological features were analyzed, and dysplasia was classified as mild, moderate, or severe. The chi(2) test was used for the following variables: gender, age, race, and smoking habits. The degree of dysplasia was related to these variables (Fisher's test) to test for independence between them (P <.05).Results: of the patient group, 72.41% were male, 75.86% were overage 40 years, 93.10% were white, and 72.41% were nonsmokers. Clinically, all patients presented with multifocal lesions. The following manifestations were seen: dryness, atrophy, scaly lesions, swelling of the lip, erythema, ulceration, blurred demarcation between the lip vermilion border and the skin, marked folds along the lip vermilion, white spots or plaques, crusts, blotchy areas, and areas of pallor. Keratosis, granulosis, hyperplasia, acanthosis, or atrophy and dysplasia were found in the epithelial tissue; elastosis, inflammatory infiltrate, and vasodilatation were found in the connective tissue. Dysplasia was mild in 10.34% of the patients, moderate in 27.59%, and severe in 62.07%. Absence of sample homogeneity was observed in regard to gender, age, race, and smoking habits. It was not possible to reject the hypothesis of independence between mild, moderate, or severe dysplasia and gender, age, race, and smoking habits.Conclusions: Dryness, atrophy, and scaly lesions were the most common clinical findings observed. Dysplasia, inflammatory infiltrate, and vasodilatation, as well as elastosis, were the most common histological findings observed. Gender, age, race, or smoking habits were not related to the degree of dysplasia in the sample. (c) 2008 American Association of Oral and Maxillofacial Surgeons.